A cross-sectional analysis of patient-reported awareness, management, and understandings of diabetes and hypertension among cataract patients in rural southern Honduran communities - King, Amber Loren Ong (International Journal Of Community Medicine And Public Health, 2017)
Background: In Honduras, the prevalence of cataracts, the leading cause of blindness, is rapidly mounting as associated chronic conditions, diabetes and hypertension, are on the rise. The increased demand for cataract surgeries has had the most severe impact on rural communities, as the majority of ophthalmologists serve cities. Additionally, owing to rural healthcare barriers, many rural dwellers have uncontrolled hypertension and diabetes, and consequently, are denied surgical candidacy due to increased surgical risk. Thus, this investigation aims to curb chronic illness in rural Honduran cataract patients by evaluating patient-reported prevalence, management, and local understandings of diabetes and hypertension in the context of socioeconomic data. Methods: The responses of cataract patients to a poverty scorecard and survey questionnaire were categorized and evaluated according to guidelines in the surrounding literature. Height, weight, blood pressure and glucose levels were also measured for each participant. Results: 22.0% and 53.7% of all study participants (n=82) were hyperglycemic and hypertensive respectively. Of the hyperglycemic patients, 38.9% had never been diagnosed with diabetes, while the remaining 61.1% appeared to have mismanaged blood glucose levels. 50% of the hypertensive patients had never been diagnosed with hypertension, and the other 50% appeared to have mismanaged blood pressure. More than half of all participants exhibited only a minimal understanding of diabetes and hypertension. Conclusions: Rural Honduran communities would benefit from regular health screenings and follow-up visits from local doctors. It is important for community health workshops to focus on informing individual health management practices and chronic illness prevention strategies.